DETERMINANTS OF CUSTOMER DEPOSITS IN THE BANKING SECTOR LISTED ON INDONESIA STOCK EXCHANGE - Jacinta Winarto; Marcellia Susan; Herlina (Modus, 2022)
ABSTRACT The customers deposits are a matter to be considered by the bank. With the tendency of this declining customer deposits raised the question, what factors have influenced the declining of the customer deposits. Looking at the previous research and facts in the field, it is assumed that the influencing factors are the  people income, the state debt securities, the interest rates and the company size. This study aims to examine and analyze the effect of people income, state debt securities, interest rates and company size on customers deposits. This research method is a quantitative method. Further, the datas are analyzed by using multiple linear regression model. The population in this study are all the banks listed at the Indonesian Stock Exchange during the period of 2013-2019. Samples are taken by using purposive sampling, obtained 33 companies. The result of this research  showed that people income, interest rates, state debt securities and company size have effect on customers deposits, so it is useful for banks to see the influence of each of the above factors that can affect changes in deposit funds in banks and to take policies based on the factors above.  Keywords: people income, state debt securities, interest rate, company size, customers deposits   ABSTRAK Simpanan nasabah merupakan hal yang harus diperhatikan oleh bank. Dengan kecenderungan menurunnya simpanan nasabah tersebut menimbulkan pertanyaan, faktor apa saja yang mempengaruhi penurunan simpanan nasabah tersebut. Melihat penelitian-penelitian sebelumnya dan fakta-fakta di lapangan, diduga bahwa faktor-faktor yang mempengaruhinya adalah pendapatan masyarakat, surat utang negara, tingkat suku bunga dan ukuran perusahaan. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh pendapatan masyarakat, surat utang negara, suku bunga dan ukuran perusahaan terhadap simpanan nasabah. Metode penelitian ini adalah metode kuantitatif. Selanjutnya data dianalisis dengan menggunakan model regresi linier berganda. Populasi dalam penelitian ini adalah seluruh bank yang terdaftar di Bursa Efek Indonesia selama periode 2013-2019. Sampel diambil dengan menggunakan purposive sampling, diperoleh 33 perusahaan. Hasil penelitian menunjukkan bahwa pendapatan masyarakat, suku bunga, surat utang negara dan ukuran perusahaan berpengaruh terhadap simpanan nasabah, sehingga berguna bagi bank untuk melihat pengaruh dari masing-masing faktor di atas yang dapat mempengaruhi perubahan dana simpanan pada bank, dan mengambil kebijakan berdasarkan faktor-faktor di atas. Kata kunci:  pendapatan masyarakat; surat utang negara; tingkat bunga; ukuran perusahaan; simpanan pelanggan